1981
DOI: 10.1289/ehp.8142187
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity and tissue distribution of lead acetate in weanling and adult rats.

Abstract: The relative toxicity of low doses of lead acetate provided steadily in drinking water or by mouth once per week was studied in weanling and adult rats. Free erythrocyte protoporphyrin and urinary 8-aminolevulinic acid levels were measured, as well as lead levels in blood and kidney. The accumulation of lead in brain tissue and in bone (femur) was measured to determine the effect of age and schedule of administration on tissue distribution and retention of lead. Total intakes of lead during the 60-week experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…Smith et al (1992) showed that elevated concentrations of lead in kidney (fresh weight) relative to levels in blood were consistent with the presence of specific leadbinding sites in the kidney at very low levels of exposure. Rader et al (1981) observed correlations between blood lead and kidney lead, and correlations between blood lead and femur lead were found only in the rats receiving lead steadily in drinking water.…”
Section: Correlations Between Lead Concentrations In Different Tissuesmentioning
confidence: 85%
See 3 more Smart Citations
“…Smith et al (1992) showed that elevated concentrations of lead in kidney (fresh weight) relative to levels in blood were consistent with the presence of specific leadbinding sites in the kidney at very low levels of exposure. Rader et al (1981) observed correlations between blood lead and kidney lead, and correlations between blood lead and femur lead were found only in the rats receiving lead steadily in drinking water.…”
Section: Correlations Between Lead Concentrations In Different Tissuesmentioning
confidence: 85%
“…The young monkeys retained 64.5 and 69.8% of the orally administered 210 Pb at 70 and 150 days of age, respectively, while adult monkeys retained 3.2% of the 210Pb dose (Castellino and Aloj, 1964;Wiles et al, 1977). In general, daily exposure to lead via drinking water resulted in the highest lead content in blood, brain, kidney, and femur for both weanling and adult rats (Rader et al, 1981). Experiments with rats showed the main storage organs: kidneys and bone.…”
Section: Distribution Of Lead In the Different Tissuesmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, analysis of the factors that affect the differences in the lead isotope ratios among the biological samples from the same person is challenging. Moreover, a number of factors could cause a redistribution of lead within the body after lead exposure [11]. It is not known whether there is fractionation of the four stable isotopes of lead during the absorption, distribution, metabolism, and excretion processes in the body.…”
Section: Introductionmentioning
confidence: 99%